Little Fists for Social Justice: Anti-Semitism, Community, and Montréal’s Aberdeen School Strike, 1913 - MacLeod, Roderick; Poutanen, Mary (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2012)
Abstract In February 1913, when a teacher at Montreal’s Aberdeen School made disparaging remarks about her Jewish pupils, five boys called a strike. Hundreds of Jewish children congregated in the park across from the school where they appointed strike leaders, established a negotiating committee, and resolved not to return to class until the teacher apologized. Some of them marched to the Baron de Hirsch Institute and the newspaper office of the Keneder Adler to demand that action be taken. The Aberdeen students showed maturity in their understanding of “the strike” as a strategic response to perceived injustice, their politicization with respect to relations between the Jewish and Anglo-Protestant communities, and class consciousness. The years 1912 and 1913 had been arduous for working-class Jews living along the St-Laurent Street corridor who experienced a lengthy tailors’ strike followed by an economic depression. The youthful strikers were acutely aware of the difficulties of being both working class and Jewish. We argue that the collective actions of the Aberdeen School strikers reveal a close connection to the labour activism of their parents and to the downtown Jewish community. Their response to the teacher’s anti-Semitic comments is an example of the historical agency of children.